Comparative Analysis and Security Issues in Broadband Wireless Networks (Global Journals of Research in Engineering, 2012)
Broadband wireless networks are considered to be enterprise-level networks providing more capacity and coverage Wireless networking has offered an alternative solution to the problem of information access in remote inaccessible areas where wired networks are not cost effective They have changed the way people communicate and share information by eliminating worrisome factors of distance and location This paper provides a technical analysis of alternatives for implementing last-mile wireless broadband services It provides detailed technical differences between 802 11 Wi-FI wireless networks with 802 16 WiMAX a new technology that solves many of the difficulties in last-mile implementations
Keywords: Broadband wireless; Last mile access; Rural connectivity; WiMAX; Wi-Fi; Digital divide; Network Security